Elevated blood pressure in youth in pediatric weight management programs in the Pediatric Obesity Weight Evaluation Registry (POWER) - Helen J. Binns; Madeline Joseph; Adolfo J. Ariza; Suzanne E. Cuda; Asheley C. Skinner; Haolin Xu; Jared M. Tucker; Sarah E. Hampl; Melissa Santos; Shawyntee Mayo; Eileen C. King; Shelley Kirk; et al. (The Journal of Clinical Hypertension, 2022)
Abstract Blood pressure (BP) assessment and management are important aspects of care for youth with obesity. This study evaluates data of youth with obesity seeking care at 35 pediatric weight management (PWM) programs enrolled in the Pediatric Obesity Weight Evaluation Registry (POWER). Data obtained at a first clinical visit for youth aged 3–17 years were evaluated to: (1) assess prevalence of BP above the normal range (high BP); and (2) identify characteristics associated with having high BP status. Weight status was evaluated using percentage of the 95th percentile for body mass index (%BMIp95); %BMIp95 was used to group youth by obesity class (class 1, 100% to < 120% %BMIp95; class 2, 120% to < 140% %BMIp95; class 3, ≥140% %BMIp95; class 2 and class 3 are considered severe obesity). Logistic regression evaluated associations with high BP. Data of 7943 patients were analyzed. Patients were: mean 11.7 (SD 3.3) years; 54% female; 19% Black non‐Hispanic, 32% Hispanic, 39% White non‐Hispanic; mean %BMIp95 137% (SD 25). Overall, 48.9% had high BP at the baseline visit, including 60.0% of youth with class 3 obesity, 45.9% with class 2 obesity, and 37.7% with class 1 obesity. Having high BP was positively associated with severe obesity, older age (15–17 years), and being male. Nearly half of treatment‐seeking youth with obesity presented for PWM care with high BP making assessment and management of BP a key area of focus for PWM programs.